Nano attapulgite loaded and modified copper-based catalyst as well as preparation method and application thereof

By using a copper-based catalyst supported by nano-concave and concave rock stone, the dehydrogenation of 1,5-pentanediol to form δ-valerol under normal pressure conditions, solving the problems of safety hazards, difficulty in separation and high catalyst cost in the prior art, and achieving efficient, stable and economical δ-valerolone synthesis.

CN119588365APending Publication Date: 2025-03-11LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411643194.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing method of producing δ-valerol through 1,5-pentanediol has problems such as safety hazards, difficulty in separation, and high catalyst cost.

Method used

Using a copper-based catalyst modified from nano-concave and concave rock stone, a catalytic reaction was carried out under normal pressure, and nano-metal Cu and rare earth metal oxides were used as the loading phase to uniformly load the carrier nano-concave and concave rock stone.

Benefits of technology

It is realized efficiently and stably catalyzed 1,5-pentanediol dehydrogenation under mild reaction conditions to prepare delta-valerol, reducing the catalyst cost, improving the safety of the reaction and the convenience of separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588365A_ABST
    Figure CN119588365A_ABST
Patent Text Reader

Abstract

The invention discloses a nano attapulgite loaded and modified copper-based catalyst and a preparation method and application thereof.The copper-based catalyst is characterized in that nano metal Cu and rare earth metal oxide are used as loading phases to be uniformly loaded on a carrier nano attapulgite ATP, the loading phases are recorded as aCubMOx / cATP catalyst, a represents the mass percent value of Cu, b represents the mass percent value of rare earth metal oxide, and c represents the mass percent value of rare earth metal oxide; b represents the mass percent value of the rare earth oxide, and c represents the mass percent value of the nano attapulgite; the mass percent of the Cu is 5-40%; the mass percent of the rare earth oxide is 0.3-9%. The catalyst can catalyze dehydrocyclization of 1, 5-pentanediol under mild conditions to prepare a delta-valerolactone product, the product yield is high, the catalyst stability is good, the preparation method is simple and convenient, the production cost is low, and industrialization is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a copper-based catalyst, in particular to a copper-based catalyst loaded and modified by nano-attapulgite, and a preparation method and application thereof. Background Art

[0002] δ-Valerolactone is a colorless or light yellow liquid with a special fruity aroma. As an important fine chemical intermediate, it is widely used in degradable polyurethanes, degradable plastic monomers, polyvalerolactone polyols, biopharmaceutical materials, coatings, inks and detergents. It can not only undergo self-polymerization at a suitable temperature to generate polycyclopentanolactone with good biodegradability, but also undergo ring-opening polymerization with other compounds. Therefore, it has a wide range of uses in environmental protection, pharmaceuticals, fluorine chemicals, degradable biomaterials, etc., and has important economic and social benefits.

[0003] There are many ways to synthesize δ-valerolactone. At present, the most mature method for synthesizing δ-cyclopentanolactone is the Baeyer-Villiger oxidation reaction with cyclopentanone as the raw material. This process is divided into peroxide acid oxidation, hydrogen peroxide oxidation, molecular oxygen oxidation and enzyme-catalyzed oxidation according to the source of oxygen-containing free radicals. However, the traditional process is too expensive, and the reaction process often involves strong oxidants such as peracids, halogen oxides, nitrogen oxides or composite oxides. The operation is dangerous and produces a large amount of pollutants, which does not meet the requirements of sustainable development and the concept of green chemistry. Other methods include hydrogen peroxide oxidation, biological oxidation, 1,5-pentanediol dehydrogenation, etc. Among them, the hydrogen peroxide oxidation reaction itself will produce water, resulting in partial hydrolysis of δ-valerolactone, so the selectivity is low and the yield is very poor. The enzymes used in the biological oxidation method, many problems such as enzyme activity, stability and manufacturing cost have not been completely solved, and they only remain in the laboratory stage. Therefore, it is of great significance to develop a new production process that is green, economical and low-pollution.

[0004] Chinese patent CN101157677 discloses a method for generating δ-valerolactone by dehydrogenation of 1,5-pentanediol. The method uses a supported nano-gold catalyst and synthesizes δ-valerolactone by oxidation reaction with high-pressure air under the solvent condition of tributyl phosphate. The method uses precious metals as catalysts, and the production cost is high; the reaction conditions are harsh, and the oxidation reaction needs to be carried out under high pressure (8-10MPa), which has high requirements for production equipment. In addition, the method requires the use of a large amount of solvent, which increases the difficulty and cost of separation, and the water produced in the reaction will cause the hydrolysis of δ-valerolactone, affecting the yield and selectivity of the reaction.

[0005] Chinese patent CN107602516A discloses a method for synthesizing δ-cyclopentanolactone catalyzed by amino acid ionic liquids, which uses H2O2 as an oxidant to assist the amino acid ionic liquid catalytic reaction and utilizes oxidation reaction to generate δ-cyclopentanolactone. The catalyst has a yield of 77%. However, the ionic liquid used is difficult to recycle and difficult to separate from the product, which makes purification too difficult and brings high separation costs, which is not conducive to industrial-scale production.

[0006] Chinese patent CN103980241B discloses a method for generating δ-valerolactone by dehydrogenation of 1,5-pentanediol as a raw material. The method uses a copper-based catalyst and modifies the catalyst with metallic silver. The reaction raw material 1,5-pentanediol needs to enter a drying tower for drying pretreatment. Although the patent can achieve a higher yield of δ-valerolactone, the price of the catalyst modification aid and carrier is high, and the product production cost is high. Summary of the invention

[0007] The purpose of the present invention is to provide a copper-based catalyst modified by loading nano-attapulgite, and a preparation method and application thereof, which solves the problems of potential safety hazards, great separation difficulty, high catalyst cost, etc. in the existing method of generating δ-valerolactone through 1,5-pentanediol. The catalyst of the present invention can obtain a high-δ-valerolactone product under relatively mild normal pressure conditions, and the catalyst of the present invention has high stability and a high catalytic reaction yield.

[0008] In order to achieve the above object, the present invention provides a copper-based catalyst modified by nano-attapulgite loading, wherein the copper-based catalyst is uniformly loaded on the carrier nano-attapulgite ATP with nano-metal Cu and rare earth metal oxide as loading phases, denoted as aCubMO x / cATP catalyst, wherein a represents the mass percentage of Cu, b represents the mass percentage of rare earth oxide, and c represents the mass percentage of nano-attapulgite; the mass percentage of Cu is 5-40%; and the mass percentage of rare earth oxide is 0.3-9%.

[0009] The second object of the present invention is to provide a method for preparing the copper-based catalyst modified by nano-attapulgite loading, which comprises: mixing nano-attapulgite ATP, Cu precursor and rare earth metal oxide precursor in water, dropping a precipitant under stirring until the pH is 10-12, aging and stirring at room temperature for 1-6 hours, filtering and washing to pH=7 after the reaction is completed, and drying; then, calcining the dried sample at 120-500° C. in an air atmosphere for 2-8 hours, taking the calcined sample and placing it in a hydrogen atmosphere at 200-350° C. for reduction for 2-6 hours to obtain a supported catalyst aCubMO x / cATP.

[0010] Preferably, the precursor of Cu is selected from any one of Cu(NO3)2·3H2O, Cu(CO2CH3)2·H2O, and CuSO4; or / and, the precursor of the rare earth metal oxide is selected from one or more of chlorides, sulfates, nitrates, phosphates, acetates, and hydrates of holmium, cerium, yttrium, and lanthanide metals; or / and, the precipitant is selected from one or more aqueous solutions of potassium carbonate, potassium bicarbonate, tetramethylammonium hydroxide, sodium hydroxide, sodium oxalate, sodium carbonate, potassium hydroxide, sodium bicarbonate, urea, ammonium carbonate, and ammonia water.

[0011] Preferably, the dropping speed of the precipitant is 4 to 16 mL / min.

[0012] Preferably, the drying temperature is 80-120°C.

[0013] Preferably, the hydrogen atmosphere is a hydrogen and inert gas atmosphere containing 5 to 100% hydrogen gas volume fraction.

[0014] More preferably, the rate of introducing the hydrogen atmosphere is 100 mL / min.

[0015] The third object of the present invention is to provide the use of the copper-based catalyst in catalyzing the dehydrogenation cyclization of 1,5-pentanediol to produce δ-valerolactone, the reaction is as follows:

[0016]

[0017] Preferably, the copper-based catalyst is used in a fixed bed reactor to dehydrogenate 1,5-pentanediol to generate δ-valerolactone. Under normal pressure to 0.5 MPa H2, 1,5-pentanediol is added through a feed pump, and the mass space velocity of 1,5-pentanediol feed is 0.2 to 0.8 h -1 , the molar ratio of hydrogen to oil (1,5-pentanediol) is 10 to 100:1, the catalytic reaction temperature is 240 to 290° C., and the dehydrogenation cyclization catalytic reaction is carried out.

[0018] The copper-based catalyst modified by nano-attapulgite loading and the preparation method and application thereof of the present invention solve the problems of potential safety hazards, great separation difficulty, high catalyst cost, etc. in the existing method of generating δ-valerolactone by 1,5-pentanediol, and has the following advantages:

[0019] (1) The present invention adopts a copper-based catalyst modified by nano-attapulgite loading, fully utilizing the alkalinity of magnesium oxide in the attapulgite carrier to promote the dehydrogenation of the raw material, and efficiently and stably catalyzes the dehydrogenation of 1,5-pentanediol to prepare δ-valerolactone under mild reaction conditions, with safe operation and low production risk;

[0020] (2) The present invention uses a copper-based catalyst modified by nano-attapulgite loading, and the catalyst does not need to be added with a precious metal additive, and the attapulgite carrier is cheap and readily available, which can significantly reduce the catalyst cost;

[0021] (3) The present invention adopts a copper-based catalyst modified by nano-attapulgite loading, and the catalyst preparation method is simple, which is convenient for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a 200h stability experiment of the 20Cu5Ho2O35Ce2O3 / 70ATP catalyst of Example 10 of the present invention.

[0023] Figure 2 This is a 80h stability experiment of the 20Cu / 80ATP catalyst of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] It should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.

[0026] In the present invention, all features defined in the form of numerical ranges or percentage ranges, such as values, quantities, contents and concentrations, are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0027] The features mentioned in the present invention can be combined arbitrarily, as long as there is no contradiction in the combination of these features, all possible combinations should be considered as the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.

[0028] Example 1

[0029] 9g of nano-attapulgite, 1.305g of Ho(NO3)3·6H2O and 1.902g of Cu(NO3)2·3H2O were dissolved in 157mL of deionized water, which was recorded as solution A. Na2CO3 was dissolved in deionized water to prepare an aqueous solution with a mass fraction of 5wt%, which was recorded as solution B. Solution A was stirred at room temperature for 1h, and then solution B was added thereto at a rate of 16mL / min until pH=11. After the addition was completed, the solution was stirred and aged at room temperature for 2h, filtered, washed 6 times until pH=7, and dried at 80℃ overnight to obtain a solid. The solid obtained above was calcined at 300℃ in air atmosphere for 3h, and then pressed into a tablet and ground into a specified mesh size to obtain a catalyst to be reduced. 4g of the catalyst to be reduced was added to a fixed bed reactor, and a H2-N2 mixed gas containing 20% ​​H2 by volume was introduced thereto at 100mL / min for reduction at 200℃ for 2h. The obtained catalyst was recorded as 5Cu5Ho2O3 / 90ATP catalyst. The catalytic reaction was directly carried out in the fixed bed reactor of the above-mentioned reduction catalyst. After the reduction was completed, the temperature was lowered to the catalytic reaction temperature. After pure hydrogen gas was introduced to replace the atmosphere inside the fixed bed reactor, the temperature was kept at 0.1 MPa for 0.2 h. -1 1,5-pentanediol was added thereto at a mass space velocity of 30:1, the hydrogen-to-oil molar ratio was 30:1, the catalytic reaction temperature was 240°C, and the catalytic reaction results are shown in Table 1.

[0030] Example 2

[0031] 8.8g of nano-attapulgite, 0.522g of Ho(NO3)3·6H2O and 3.805g of Cu(NO3)2·3H2O were dissolved in 315mL of deionized water, which was recorded as solution A. K2CO3 was dissolved in deionized water to prepare a 5wt% aqueous solution, which was recorded as solution B. Solution A was stirred at room temperature for 5h, and then solution B was added thereto at a rate of 4mL / min until pH = 10. After the addition was complete, the solution was stirred and aged at room temperature for 5h, filtered, washed 4 times until pH = 7, and dried at 120℃ overnight to obtain a solid.

[0032] The solid obtained above was calcined at 120°C in air atmosphere for 3h, then pressed into tablets and ground into a specified mesh size to obtain the catalyst to be reduced. 4g of the catalyst to be reduced was added to a fixed bed reactor, and a H2-N2 mixed gas containing 5% H2 by volume was introduced at 100mL / min to reduce it at 350°C for 2h. The obtained catalyst was recorded as 10Cu2Ho2O3 / 88ATP catalyst. The catalytic reaction was directly carried out in the fixed bed reactor of the above-mentioned reduced catalyst. After the reduction was completed, the temperature was lowered to the catalytic reaction temperature, and pure hydrogen gas was introduced to replace the internal atmosphere of the fixed bed reactor. Then, the reaction mixture was heated at room temperature for 0.4h under normal pressure. -11,5-pentanediol was added thereto at a mass space velocity of 50:1, the hydrogen-to-oil molar ratio was 50:1, the reaction temperature was 240°C, and the catalytic reaction results are shown in Table 1.

[0033] Example 3

[0034] 5.5g of nano-attapulgite, 1.305g of Ho(NO3)3·6H2O and 15.089g of Cu(NO3)2·3H2O were dissolved in 788mL of deionized water, which was recorded as solution A. H2C2O4 and NaHCO3 were dissolved in deionized water to prepare a sodium oxalate aqueous solution with a mass fraction of 5wt%, which was recorded as solution B. Solution A was stirred at room temperature for 2h, and then solution B was added thereto at a speed of 12mL / min until pH = 10. After the addition was completed, the solution was stirred and aged at room temperature for 4h, filtered, washed 4 times until pH = 7, and dried at 90℃ overnight to obtain a solid.

[0035] The solid obtained above was calcined at 350°C in air atmosphere for 3h, then pressed into tablets and ground into a specified mesh size to obtain the catalyst to be reduced. 4g of the catalyst to be reduced was added to a fixed bed reactor, and a H2-N2 mixed gas containing 50% H2 by volume was introduced at 100mL / min to reduce it at 350°C for 2h. The obtained catalyst was recorded as 40Cu5Ho2O3 / 55ATP catalyst. The catalytic reaction was directly carried out in the fixed bed reactor of the above-mentioned reduced catalyst. After the reduction was completed, the temperature was lowered to the catalytic reaction temperature, and pure hydrogen gas was introduced to replace the internal atmosphere of the fixed bed reactor. Then, the reaction mixture was heated at 0.5MPa for 0.6h. -1 1,5-pentanediol was added thereto at a mass space velocity of 40:1, the hydrogen-to-oil molar ratio was 40:1, the reaction temperature was 290°C, and the catalytic reaction results are shown in Table 1.

[0036] Example 4

[0037] 7.5g of nano-attapulgite, 1.262g of Ce(NO3)3·6H2O and 7.609g of Cu(NO3)2·3H2O were dissolved in 630mL of deionized water, which was recorded as solution A. K2CO3 was dissolved in deionized water to prepare a 5wt% aqueous solution, which was recorded as solution B. Solution A was stirred at room temperature for 2h, and then solution B was added thereto at a rate of 8mL / min until pH = 10. After the addition was completed, the solution was stirred and aged at room temperature for 4h, filtered, washed 3 times until pH = 7, and dried at 120℃ overnight to obtain a solid.

[0038] The solid obtained above was calcined at 240°C in air atmosphere for 2h, then pressed into tablets and ground into a specified mesh size to obtain the catalyst to be reduced. 4g of the catalyst to be reduced was added to a fixed bed reactor, and a H2-N2 mixed gas containing 60% H2 by volume was introduced at 100mL / min to reduce it at 270°C for 2h. The obtained catalyst was recorded as 20Cu5Ce2O3 / 75ATP catalyst. The catalytic reaction was directly carried out in the fixed bed reactor of the above-mentioned reduced catalyst. After the reduction was completed, the temperature was lowered to the catalytic reaction temperature, and pure hydrogen gas was introduced to replace the internal atmosphere of the fixed bed reactor. Then, the reaction mixture was heated at 0.3MPa for 0.3h. -1 1,5-pentanediol was added thereto at a mass space velocity of , a hydrogen-to-oil molar ratio of 10:1, a reaction temperature of 290°C, and the catalytic reaction results are shown in Table 1.

[0039] Example 5

[0040] 7.5g of nano-attapulgite, 1.696g of Y(NO3)3·6H2O and 7.609g of Cu(NO3)2·3H2O were dissolved in 630mL of deionized water, which was recorded as solution A. CO(NH2)2 was dissolved in deionized water to prepare a 5wt% aqueous solution, which was recorded as solution B. Solution A was stirred at room temperature for 4h, and then solution B was added thereto at a rate of 12mL / min until pH = 10. After the addition was complete, the solution was stirred and aged at room temperature for 5h, filtered, washed 5 times until pH = 7, and dried at 110℃ overnight to obtain a solid.

[0041] The solid obtained above was calcined at 310°C in air atmosphere for 5h, then pressed into tablets and ground into a specified mesh size to obtain the catalyst to be reduced. 4g of the catalyst to be reduced was added to a fixed bed reactor, and a H2-N2 mixed gas containing 50% H2 by volume was introduced at 100mL / min to reduce it at 350°C for 2h. The obtained catalyst was recorded as 20Cu5Y2O3 / 75ATP catalyst. The catalytic reaction was directly carried out in the fixed bed reactor of the above-mentioned reduced catalyst. After the reduction was completed, the temperature was lowered to the catalytic reaction temperature, and pure hydrogen gas was introduced to replace the internal atmosphere of the fixed bed reactor. Then, the reaction mixture was heated at 0.1MPa for 0.8h. -1 1,5-pentanediol was added thereto at a mass space velocity of , the hydrogen-to-oil molar ratio was 90:1, the reaction temperature was 250°C, and the catalytic reaction results are shown in Table 1.

[0042] Example 6

[0043] 7.5g of nano-attapulgite, 1.329g of La(NO3)3·6H2O and 7.609g of Cu(NO3)2·3H2O were dissolved in 630mL of deionized water, which was recorded as solution A. NaOH was dissolved in deionized water to prepare a 5wt% aqueous solution, which was recorded as solution B. Solution A was stirred at room temperature for 1h, and then solution B was added thereto at a rate of 16mL / min until pH = 12. After the addition was completed, the solution was stirred and aged at room temperature for 2h, filtered, washed 4 times until pH = 7, and dried at 100℃ overnight to obtain a solid.

[0044] The solid obtained above was calcined at 500°C in air atmosphere for 3h, then pressed into tablets and ground into a specified mesh size to obtain the catalyst to be reduced. 4g of the catalyst to be reduced was added to a fixed bed reactor, and a H2-N2 mixed gas containing 20% ​​H2 by volume was introduced at 100mL / min to reduce it at 200°C for 2h. The obtained catalyst was recorded as 20Cu5La2O3 / 75ATP catalyst. The catalytic reaction was directly carried out in the fixed bed reactor of the above-mentioned reduced catalyst. After the reduction was completed, the temperature was lowered to the catalytic reaction temperature, and pure hydrogen gas was introduced to replace the internal atmosphere of the fixed bed reactor. Then, the reaction temperature was kept at 0.2MPa for 0.7h. -1 1,5-pentanediol was added thereto at a mass space velocity of , the hydrogen-to-oil molar ratio was 100:1, the reaction temperature was 260°C, and the catalytic reaction results are shown in Table 1.

[0045] Example 7

[0046] 7.97g of nano-attapulgite, 0.084g of Ho(NO3)3·6H2O and 7.609g of Cu(NO3)2·3H2O were dissolved in 630mL of deionized water, which was recorded as solution A. (NH4)2CO3 was dissolved in deionized water to prepare a 5wt% aqueous solution, which was recorded as solution B. Solution A was stirred at room temperature for 2h, and then solution B was added thereto at a rate of 10mL / min until pH = 10. After the addition was completed, the solution was stirred and aged at room temperature for 4h, filtered, washed 6 times until pH = 7, and dried at 110℃ overnight to obtain a solid.

[0047] The solid obtained above was calcined at 230°C in air atmosphere for 4 hours, and then pressed into tablets and ground into a specified mesh size to obtain the catalyst to be reduced. 4 g of the catalyst to be reduced was added to a fixed bed reactor, and a H2-N2 mixed gas containing 20% ​​H2 by volume was introduced at 100 mL / min to reduce it at 300°C for 2 hours. The obtained catalyst was recorded as 20Cu0.3Ho2O3 / 79.7ATP catalyst. The catalytic reaction was directly carried out in the fixed bed reactor of the above-mentioned reduced catalyst. After the reduction was completed, the temperature was lowered to the catalytic reaction temperature, and pure hydrogen gas was introduced to replace the internal atmosphere of the fixed bed reactor. Then, under the condition of 0.3 MPa, the temperature was kept at 0.3 h.-1 1,5-pentanediol was added thereto at a mass space velocity of 40:1, the hydrogen-to-oil molar ratio was 40:1, the reaction temperature was 250°C, and the catalytic reaction results are shown in Table 1.

[0048] Example 8

[0049] 6.8g of nano-attapulgite, 1.828g of Ho(NO3)3·6H2O, 1.262g of Ce(NO3)3·6H2O and 7.609g of Cu(NO3)2·3H2O were dissolved in 630mL of deionized water, which was recorded as solution A. KOH was dissolved in deionized water to prepare an aqueous solution with a mass fraction of 5wt%, which was recorded as solution B. Solution A was stirred at room temperature for 4h, and then solution B was added thereto at a speed of 8mL / min until pH = 12. After the addition was completed, the solution was stirred and aged at room temperature for 5h, filtered, washed 3 times until pH = 7, and dried at 120℃ overnight to obtain a solid.

[0050] The solid obtained above was calcined at 330°C in air atmosphere for 3h, then pressed into tablets and ground into a specified mesh size to obtain the catalyst to be reduced. 4g of the catalyst to be reduced was added to a fixed bed reactor, and high-purity hydrogen was introduced at 100mL / min to reduce it at 270°C for 2h. The obtained catalyst was recorded as 20Cu7Ho2O35Ce2O3 / 68ATP catalyst. The catalytic reaction was directly carried out in the fixed bed reactor of the above-mentioned reduced catalyst. After the reduction was completed, the temperature was lowered to the catalytic reaction temperature, and pure hydrogen gas was introduced to replace the internal atmosphere of the fixed bed reactor. Then, under the condition of 0.1MPa, the temperature was kept at 0.6h. -1 1,5-pentanediol was added thereto at a mass space velocity of , a hydrogen-to-oil molar ratio of 100:1, a reaction temperature of 270°C, and the catalytic reaction results are shown in Table 1.

[0051] Example 9

[0052] 7.1g of nano-attapulgite, 2.357g of Ho(NO3)3·6H2O and 7.609g of Cu(NO3)2·3H2O were dissolved in 630mL of deionized water, which was recorded as solution A. 25wt% NH3·H2O was diluted to a 5wt% aqueous solution, which was recorded as solution B. Solution A was stirred at room temperature for 3h, and then solution B was added thereto at a rate of 16mL / min until pH = 10. After the addition was complete, the solution was stirred and aged at room temperature for 3h, filtered, washed 5 times until pH = 7, and dried at 80℃ overnight to obtain a solid.

[0053] The solid obtained above was calcined at 350°C in air atmosphere for 2h, then pressed into tablets and ground into a specified mesh size to obtain the catalyst to be reduced. 4g of the catalyst to be reduced was added to a fixed bed reactor, and a H2-N2 mixed gas containing 80% H2 by volume was introduced at 100mL / min to reduce it at 350°C for 2h. The obtained catalyst was recorded as 20Cu9Ho2O3 / 71ATP catalyst. The catalytic reaction was directly carried out in the fixed bed reactor of the above-mentioned reduced catalyst. After the reduction was completed, the temperature was lowered to the catalytic reaction temperature, and pure hydrogen gas was introduced to replace the internal atmosphere of the fixed bed reactor. Then, the reaction mixture was heated at 0.4h under 0.3MPa. -1 1,5-pentanediol was added thereto at a mass space velocity of 50:1, the hydrogen-to-oil molar ratio was 50:1, the reaction temperature was 270°C, and the catalytic reaction results are shown in Table 1.

[0054] Example 10

[0055] 7.0g of nano-attapulgite, 1.305g of Ho(NO3)3·6H2O, 1.262g of Ce(NO3)3·6H2O and 6.246g of Cu(Ac)2·H2O were dissolved in 630mL of deionized water, which was recorded as solution A. Na2CO3 was dissolved in deionized water to prepare a 5wt% aqueous solution, which was recorded as solution B. Solution A was stirred at room temperature for 5h, and then solution B was added thereto at a rate of 8mL / min until pH = 10. After the addition was complete, the solution was stirred and aged at room temperature for 6h, filtered, washed 3 times until pH = 7, and dried at 100℃ overnight to obtain a solid.

[0056] The solid obtained above was calcined at 340°C in air atmosphere for 4 hours, and then pressed into tablets and ground into a specified mesh size to obtain the catalyst to be reduced. 4g of the catalyst to be reduced was added to a fixed bed reactor, and a H2-N2 mixed gas containing 50% H2 by volume was introduced at 100mL / min to reduce it at 300°C for 2 hours. The obtained catalyst was recorded as 20Cu5Ho2O35Ce2O3 / 70ATP catalyst. The catalytic reaction was directly carried out in the fixed bed reactor of the above-mentioned reduced catalyst. After the reduction was completed, the temperature was lowered to the catalytic reaction temperature, and pure hydrogen gas was introduced to replace the internal atmosphere of the fixed bed reactor. Then, under the condition of 0.5MPa, the temperature was kept at 0.35h -1 1,5-pentanediol was added thereto at a mass space velocity of 60:1, a hydrogen-to-oil molar ratio of 60:1, a reaction temperature of 250°C, and the catalytic reaction results are shown in Table 1. The stability of the 20Cu5Ho2O35Ce2O3 / 70ATP catalytic reaction for 200h of Example 10 of the present invention is shown in Table Figure 1 .

[0057] Comparative Example 1

[0058] 8g of nano-attapulgite and 7.609g of Cu(NO3)2·3H2O were dissolved in 630mL of deionized water, which was recorded as solution A. Na2CO3 was dissolved in deionized water to prepare a 5wt% aqueous solution, which was recorded as solution B. Solution A was stirred at room temperature for 5h, and then solution B was added thereto at a rate of 8mL / min until pH = 10. After the addition was completed, the solution was stirred and aged at room temperature for 6h, filtered, washed 3 times until pH = 7, and dried at 120°C overnight to obtain a solid.

[0059] The solid obtained above was calcined at 320°C in air atmosphere for 4 hours, and then pressed into tablets and ground into a specified mesh size to obtain the catalyst to be reduced. 4g of the catalyst to be reduced was added to a fixed bed reactor, and a H2-N2 mixed gas containing 50% H2 by volume was introduced at 100mL / min to reduce it at 200°C for 2 hours. The obtained catalyst was recorded as 20Cu / 80ATP catalyst. The catalytic reaction was directly carried out in the fixed bed reactor of the above-mentioned reduced catalyst. After the reduction was completed, the temperature was lowered to the catalytic reaction temperature, and pure hydrogen gas was introduced to replace the internal atmosphere of the fixed bed reactor. Then, under the condition of 0.1MPa, the temperature was kept at 0.4h. -1 1,5-pentanediol was added thereto at a mass space velocity of 60:1, a hydrogen-to-oil molar ratio of 60:1, a reaction temperature of 270°C, and the catalytic reaction results are shown in Table 1. The stability of the 20Cu / 80ATP catalytic reaction for 80 hours in Comparative Example 1 of the present invention is shown in Table Figure 2 .

[0060] Table 1 is Cu-MO x / ATP reaction conditions and activity results

[0061]

[0062] By analyzing Examples 1 to 10 and Comparative Example 1, it was found that the catalyst in the comparative example without rare earth oxide doping showed obvious signs of deactivation after about 50 hours of reaction, while the catalyst in Example 10 not only achieved higher conversion rate and δ-valerolactone selectivity, but also ran stably for 200 hours without obvious signs of deactivation. This indicates that the basic magnesium oxide and active Cu nanoparticles in the carrier attapulgite synergistically catalyze the dehydrogenation and cyclization of the raw materials, while the doped rare earth oxide further improves the catalyst stability, and efficiently and stably catalyzes the dehydrogenation of 1,5-pentanediol to prepare δ-valerolactone under mild reaction conditions.

[0063] The experimental results in the above table show that the use of rare earth oxide-modified nano-copper catalysts for catalyzing the dehydrogenation cyclization of 1,5-pentanediol to prepare δ-valerolactone is an effective synthetic route, and the catalyst can be reused to maintain a high activity, which has excellent industrial value.

[0064] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A copper-based catalyst modified by nano-attapulgite loading, characterized in that: The copper-based catalyst is a Cu nano-metal and a rare earth metal oxide as the supporting phase uniformly loaded on the carrier nano-attapulgite ATP, denoted as aCubMO x / cATP catalyst, wherein a represents the mass percentage of Cu, b represents the mass percentage of rare earth oxide, and c represents the mass percentage of nano-attapulgite; The mass percentage of Cu is 5-40%; the mass percentage of rare earth oxide is 0.3-9%.

2. The method for preparing a copper-based catalyst modified by nano-attapulgite loading according to claim 1, characterized in that: The method includes: The precursors of nano-attapulgite ATP, Cu and rare earth metal oxides are mixed in water, and a precipitant is added dropwise under stirring until the pH value is 10 to 12, and the mixture is aged and stirred at room temperature for 1 to 6 hours. After the reaction is completed, the mixture is filtered, washed until the pH value is 7, and dried. Next, the dried sample was calcined at 120-500°C in air atmosphere for 2-8 h, and the calcined sample was reduced in hydrogen atmosphere at 200-350°C for 2-6 h to obtain the supported catalyst aCubMO x / cATP.

3. The preparation method according to claim 2, characterized in that: The Cu precursor is selected from any one of Cu(NO3)2·3H2O, Cu(CO2CH3)2·H2O, and CuSO4; or / and, the precursor of the rare earth metal oxide is one or more selected from chlorides, sulfates, nitrates, phosphates, acetates and hydrates thereof of holmium, cerium, yttrium and lanthanide metals; Or / and, the precipitant is selected from one or more aqueous solutions of potassium carbonate, potassium bicarbonate, tetramethylammonium hydroxide, sodium hydroxide, sodium oxalate, sodium carbonate, potassium hydroxide, sodium bicarbonate, urea, ammonium carbonate, and ammonia water.

4. The preparation method according to claim 2, characterized in that: The dropping speed of the precipitant is 4 to 16 mL / min.

5. The preparation method according to claim 2, characterized in that: The drying temperature is 80-120°C.

6. The preparation method according to claim 2, characterized in that: The hydrogen atmosphere is a hydrogen and inert gas atmosphere in which the hydrogen gas volume fraction is 5 to 100%.

7. The preparation method according to claim 6, characterized in that: The rate of introducing the hydrogen atmosphere was 100 mL / min.

8. Use of the copper-based catalyst as claimed in claim 1 in catalyzing the dehydrogenation cyclization of 1,5-pentanediol to produce δ-valerolactone.

9. The use according to claim 8, characterized in that: The copper-based catalyst is used in a fixed bed reactor to dehydrogenate 1,5-pentanediol to generate delta-valerolactone. Under normal pressure to 0.5 MPa H2, 1,5-pentanediol is added through a feed pump. The mass space velocity of the 1,5-pentanediol feed is 0.2 to 0.8 h -1 , the hydrogen-to-oil molar ratio is 10-100:1, the catalytic reaction temperature is 240-290°C, and the dehydrogenation cyclization catalytic reaction is carried out.

Citation Information

Patent Citations

  • Supported type nano catalyst for low temperature carbon monoxide oxidation and preparation thereof

    CN101264445A

  • Solid copper-based catalyst, preparation method and application thereof, hydrogen storage system for storing and releasing hydrogen, and method for storing and releasing hydrogen

    CN115414934A

  • Catalyst for catalyzing dehydrogenation of 1, 4-butanediol to prepare gamma-butyrolactone as well as preparation method and application of catalyst

    CN117186037A

  • Dehydrogenation catalyst as well as preparation method and application thereof

    CN117654528A